Cobrança pelo uso dos recursos hídricos na bacia hidrográfica do rio São Francisco no decênio 2011 a 2020 - Oliveira, Luiz Ricardo Santos de (2023)
Charging for the use of water resources can be understood to encourage the rational use of water, in addition to raising financial resources for investments in environmental recovery and conservation actions. However, its implementation involves technical, political, and social challenges. In the face of that, this work aimed to analyze the charging for the use of water in the San Francisco River basin (BHSF), between the years 2011 and 2020 and, in particular, to analyze the hydro-environmental recovery projects carried out in the states of Minas Gerais and Sergipe. This research was based on master's and doctoral research related to the study of water resources, in addition to scientific articles, laws, application plans, management reports, deliberations and information on charging, collection and projects executed in the BHSF, through website of the San Francisco River basin committee and of the Peixe Vivo Basin Agency. The results of the present research demonstrate that the collection in this river basin is effectively and institutionally achieving its goals, however, the available resources are not sufficient to attend the investment demands necessary to reduce the main challenges of the San Francisco River basin. It was also observed that there was a constant increase in the collection of resources from different uses between 2011 and 2018, as well as a significant growth in collection with the new methodology started in 2019, mainly in uses for irrigation and transposition. Besides, it was verified that Sergipe actively contributes to the collection of the river basin, but needsinvestment in hydro-environmental recovery projects, in contrast to Minas Gerais, which has several projects financed by the water charging and has a significant participation in the total collection of the region. Finally, although the efforts and commitment of the management organizations of the San Francisco River basin, this water resource faces significant obstacles, set by the high demand for the use of water, as well as the irregular distribution of projects to recover the river basin.